Rapid in Vitro Quantification of S. aureus Biofilms on Vascular Graft Surfaces - Herten, Monika; Bisdas, Theodosios; Knaack, Dennis; Becker, Karsten; Osada, Nani; Torsello, Giovanni B.; Idelevich, Evgeny A. (Frontiers in Microbiology, 2017)
Objectives Increasing resistance of microorganisms and particularly tolerance of bacterial biofilms against antibiotics require the need for alternative antimicrobial substances. S. aureus is the most frequent pathogen causing vascular graft infections. In order to evaluate the antimicrobial efficacy, quantification of the bacterial biofilms is necessary. Aim of the present study was the validation of an in vitro model for quantification of bacterial biofilm on vascular graft surfaces using three different assays. Methods Standardized discs of vascular graft material (Dacron or PTFE) or polystyrene (PS) as control surface with 0.25 cm2 surface area were inoculated with 10-3 diluted overnight culture of three biofilm-producing S. aureus isolates (BEB-029, BEB-295, SH1000) in 96-well PS culture plates. After incubation for 4 and 18h, the biofilm was determined by three different methods: a) mitochondrial ATP concentration as measure of bacterial viability (ATP), b) crystal violet staining (Cry), and c) vital cell count by calculation of colony-forming units (CFU). The experiments were performed three times. Quadruplicates were used for each isolate, time point and method. In parallel, bacterial biofilms were documented via scanning electron microscopy. Results All three methods could quantify biofilms on the PS control. Time needed was 0:40h, 13:10h and 14:30h for ATP, Cry, and CFU, respectively. The Cry assay could not be used for vascular graft surfaces due to high unspecific background staining. However, ATP assay and CFU count showed comparable results on vascular graft material and control. The correlations between ATP and CFU assay differed according to the surface and incubation time and were significant only after 4h on Dacron (BEB-029, p=0.013) and on PS (BEB-029, p<0.001). Between ATP and Cry assay on PS, a significant correlation could be detected after 4h (BEB-295, p=0.027) and after 18h (all three strains, (p<0.026). The reproducibility of the ATP-assay presented as inter-assay-variance of 2.1 and as intra-assay variance of 8.1 on polystyrene. Conclusion The in-vitro model reproducibly quantifies biofilm on standardized vascular graft surfaces with CFU and ATP assay as detection system. The ATP assay allows accelerated microbial quantification, however the correlation with the CFU assay may be strain- and surface-dependent.